2006
DOI: 10.1007/s10681-006-9205-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection of wheat based on economic returns per unit area

Abstract: This study aimed to investigate a cultivar selection criterion based on income ha -1 in common wheat. Regional yield trials with 20 entries were planted in Diyarbakır, Hazro and Ceylanpınar in southeast Anatolia in the 2004/ 2005 growing season. A randomized complete block design with four replications was employed. Grain samples from each location were subjected to quality analyses, and then presented to randomly selected grain purchasers with the local commodity market for market price estimations.Entries 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…As discussed by Ozberk et al (29) and Hollingsworth et al (14), wheat cultivars are often selected based on grain YLD rather than quality traits, with producers often in clined to select high-yielding, low-quality cultivars over loweryielding, higher-quality cultivars. We showed that un der the disease levels of this study (IND of 0 to 17%), the integra tion of moderate resistance and a fungicide application was suffi cient to minimize the effect of FHB on grain YLD and quality losses, without the need to change the combine harvester config uration.…”
Section: Grain Quality and Price Discounts"_______________ Gci ($Ha-'mentioning
confidence: 99%
“…As discussed by Ozberk et al (29) and Hollingsworth et al (14), wheat cultivars are often selected based on grain YLD rather than quality traits, with producers often in clined to select high-yielding, low-quality cultivars over loweryielding, higher-quality cultivars. We showed that un der the disease levels of this study (IND of 0 to 17%), the integra tion of moderate resistance and a fungicide application was suffi cient to minimize the effect of FHB on grain YLD and quality losses, without the need to change the combine harvester config uration.…”
Section: Grain Quality and Price Discounts"_______________ Gci ($Ha-'mentioning
confidence: 99%
“…SD can reflect the quantity and quality of bread or durum wheat gluten protein, and the relationships between these variables have been extensively studied (Payne 1987;MacRitchie et al 1990;Silvela et al 1993). In addition, SD is significantly correlated not only with the taste and appearance of Dry White Chinese Noodles but also with cookie diameter and market price (Özberk et al 2006;Ozturk et al 2008). A significant correlation between the sedimentation value and the mixograph score was also observed.…”
Section: Introductionmentioning
confidence: 98%
“…Wheat is the most widely grown cereal in Turkey. Turkey is home to 23 species of wild wheat and more than 400 cultivated wheat varieties [49]. Regardless of the irregular topography and various climates, it is possible to produce winter wheat in almost every region.…”
Section: Study Areamentioning
confidence: 99%